Graphic design a practical guide for librarians - Colston, Valerie (Practical guides for librarians, 2019)
This book will help librarians complete graphic design projects with creativity and skill. Written specifically for librarians, it starts with the basics of design and builds on those skills. It is a guide that is relevant to those just learning to create designs and those who have been creating visuals for many years.